2004
DOI: 10.1051/forest:2004048
|View full text |Cite
|
Sign up to set email alerts
|

Fire behaviour and severity in a maritime pine stand under differing fuel conditions

Abstract: -An experimental fire was conducted in the summer in a 28-year old maritime pine (Pinus pinaster) plantation in northeastern Portugal. Fuel conditions within the stand were age-dependent and comprised four situations: treated with prescribed fire at differing times, respectively 2, 3, and 13 years before the study, and undisturbed, where fuel accumulation time equalled stand age. The rate of fire spread did not respond to factors other than wind speed, in spite of the fuel-complex diversity. A high-intensity f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(51 citation statements)
references
References 26 publications
2
44
1
3
Order By: Relevance
“…Higher shrub loading implies higher flammability, likelihood of crowning fire, and difficulty in fire control (Schmidt et al 2002, Fernandes 2009a. Fernandes et al (2004) observed differences in fire behavior and severity among maritime pine (Pinus pinaster) plots depending on fuel age (i.e., time since last treatment) and the presence or absence of surface fuel treatments. Furthermore, recent research aimed at developing wildfire occurrence models in Portugal included the understory shrubs biomass as a significant variable.…”
Section: Introductionmentioning
confidence: 99%
“…Higher shrub loading implies higher flammability, likelihood of crowning fire, and difficulty in fire control (Schmidt et al 2002, Fernandes 2009a. Fernandes et al (2004) observed differences in fire behavior and severity among maritime pine (Pinus pinaster) plots depending on fuel age (i.e., time since last treatment) and the presence or absence of surface fuel treatments. Furthermore, recent research aimed at developing wildfire occurrence models in Portugal included the understory shrubs biomass as a significant variable.…”
Section: Introductionmentioning
confidence: 99%
“…Previous fire history was also provided by the local environmental agency, and the selected plots were not burned at least before 1967. Fuel conditions were similar in all the plots, in order to avoid differences in fire intensity and severity caused by this parameter (Fernandes et al, 2004). Finally, the plots were also comparable in terms of stand structure (Tab.…”
Section: Experimental Design and Chronosequence Plot Selectionmentioning
confidence: 93%
“…Borhidi & Fernández (11.1%). The number of recorded species was higher than that before fire (22) and homogeneous in the three plots (9 ± 1.9). It is important to note the high presence of several species that were not recorded before fire, i.e., Sorghastrum stipoides (Kunth) Nash (55.6% of total samples), Odontosoria writghiana Maxon.…”
Section: Floristic Richness and Diversitymentioning
confidence: 97%
“…Among these, fire intensity and frequency have shown to be significant variables that act on seed survival, density, mortality, height, crown area, plus basal diameters of seedlings and sprouts in tropical forests [33]. On the other hand, site quality and vegetation structure and composition before fire have to be considered as very important factors to determine the early stages of secondary succession [20,22,45].…”
Section: Discussionmentioning
confidence: 99%